The Cyclicality of Loan Loss Provision in Brazilian Commercial Banks - Antônio Maria Henri Beyle de Araújo; Paulo Roberto Barbosa Lustosa; José Alves Dantas (BBR: Brazilian Business Review, 2018)
Debates on banking regulation have increasingly given rise to a discussion on the relationship between the loan loss provision and business cycles. Provisioning rules for credit losses for banks in Brazil have mixed system characteristics, which could theoretically lead banks to pro-cyclical or countercyclical behavior, which reinforces the need for research to indicate what has actually been the effect of these provisions in the economy. The purpose of this paper is to analyze the relationship between banks’ provisioning for credit losses and business cycles in Brazil, in an attempt to confirm its nature, a condition capable of avoiding potentiating the effects of economic contraction or expansion. Using an econometric model with accounting and macroeconomic variables, the survey involved 91 commercial banks in the period from 2001 to 2012. Confirming that the delay in payments of principal and charges is a key condition for the recognition of banking provisions in Brazil, which highlights its predominantly retrospective nature, the results point to the existence of a pro-cyclical behavior by the banks surveyed, indicating that when GDP is on the rise, provisions tend to fall and vice versa.